URGENSI DAN PARADIGMA PENDIDIKAN PERSPEKTIF AL-QUR'AN SURAH AL-ALAQ - Fauziah, Neneng; Hidayat, Wahyu; Wasehudin, Wasehudin (FIKRAH, 2023)
Education is a matter of life and living. The whole process in human life and life is the education process itself. Education is so important that Allah sent down the first verse to the Prophet Muhammad SAW, which is an order for humans to read and understand the meaning and purpose of creation, implying the process of divine education (QS 96:1) and basyariah (QS 96:4). This study aims to explore the urgency and paradigm of Islamic education contained in sura al-Alaq; 1-5. The method used in this research is a literature study. The data used were obtained from relevant sources consisting of books, journals and writings. That it is important to read between the lines of this verse, in order to develop basic human potential so that they are able to carry out the mandate to become caliphs on earth and become pious servants. Education that can develop the role of humans as caliph fil ardh is education that refers to the conceptual foundation with the main teachings of aqidah and morals. It is through the basic teachings of aqidah and morals that humans become intelligent, trustworthy, responsible, and have positive values, so they can create a safe and peaceful environment.